Edukasi Gizi “Healthy Food and Life Style to Increase Working Memory Capacity” Siswi MTs (Madrasah Tsanawiyah) Al-Fatah - Afiska Prima Dewi; Ritma Dewanti; Hernianti Hernianti; Syamsopyan Syamsopyan; Suherman Suherman (PPNI UNIMMAN, 2025)
Working memory capacity is a crucial aspect of cognitive function that plays a significant role in supporting students' learning processes. Working memory functions as a temporary storage system that allows individuals to store and manipulate information quickly. In an educational context, optimal working memory capacity can improve students' ability to understand, process, and remember information presented during the teaching and learning process. Several factors known to influence working memory capacity include breakfast habits, nutritional status, body fat percentage, and hemoglobin (Hb) levels. These factors are closely related to students' daily nutritional intake and healthy lifestyle. This Community Service (PkM) activity, with the topic